(untitled) (Global Journal of Medical Research, 2014)
Breast lump is a common finding in surgical practice. The breast lump so presented should accurately diagnose in order to initiate the treatment early. In order to study the efficacy of FNAC, this study was undertaken in Outpatient department. A total of 150 patients attending the outpatient department were chosen as study sample. The sample for FNAC was obtained by using ultrasound guided needle aspiration and the tissue excised was sent to histopathological examination. The mean age group of women in this study was 34.98 years and majority of the women were aged 21 -30 years. More than half of the women in this study had lump measuring 1 -3 × 1 -3 cms. In this study, 21.3% of the breast lumps were due to benign breast disease, 56.7% of the women had fibroadenoma of the breast, 14.7% had suspicious malignancy and 7.3% had features suggestive of malignancy on FNAC examination. The comparison of FNAC findings with histopathology had shown that 17.3% of the patients who were diagnosed as benign breast disease had fibro adenoma on histopathology, 12% with suspicious malignancy turned out as invasive duct carcinoma.